The Effect of Parent Attention and Teacher's Competency on Students Learning Outcomes During Online Learning - Nugraha, Rifa; Haryadi; Setyaningsih, Nas Haryati (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2022)
Indonesian language learning content is a program to develop knowledge, language skills, and a positive attitude towards the Indonesian language itself as well as respect for humans and human values. The aims of the study were to analyze the relationship between parental attention and Indonesian language learning outcomes, the relationship between teacher competence and Indonesian learning outcomes, and the relationship between parental attention and teacher competence and Indonesian learning outcomes. This type of quantitative descriptive research. The research population was 344 students of class V elementary school. The research sample was 185 students with random sampling technique. Data collection techniques using questionnaires and documentation. Data analysis using descriptive statistics and inferential statistics. The results of the study showed that there was no positive and significant relationship between parental attention and the results of learning Indonesian, because the sig score of 0.152 was more than 0.05. There is a significant positive relationship between teacher competency and Indonesian language learning outcomes, because the sig 0.004 score is less than 0.05. There is a jointly significant positive relationship between parental attention and teacher competency with Indonesian language learning outcomes, because the sig or 0.013 result is less than 0.05. Based on the discussion and conclusions, several suggestions can be put forward, including that parents play a very important role in the child's learning process, especially in this case the Indonesian language subject. Therefore, parents must pay attention to their child's learning process.